Cash flow forecasting and liquidity - Coyle, Brian; Chartered Institute of Bankers (Canterbury : CIB Publishing, 2000)
The book examines the value of money in the context of achieving sound cash flow for any business. It explains the need to control cash, to consider the income earned by investing it and the shrinkage caused by inflation or exchange rate movements. This is with the aim of explaining how cash is controlled and non-interest earning balances are kept to a minimum.
Includes index.
Library edition published by Glenlake/ Fitzroy Dearborn Publishers, 2000
oif 17/07/14; 31/08/15
Loan
Keywords: Cash flow; Cash flow - forecasting; Liquidity (Economics); Cash management